(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Abbas B, Mawikere NL, Tjolli I, Arsyad M, Munarti. 2021. Molecular characteristic on intra-species of Metroxylon sagu from Papua, Indonesia by nad2 and matK genes. Biodiversitas 22: 5302-5310. Sago palm (Metroxylon sagu Rottb.) is a palm that is capable accumulated a lot of starch for food in the trunk. The molecular characterization of sago palm is very important as identities of biological existence in the certain areas. This study aimed to reveal molecular characteristic on intra-species of M. sagu from Papua based on NADH dehydrogenase subunit 2 (nad2) gene and maturase K (matK) gene. 15 accessions were used in this study. Sequences of nad2 gene on some accessions of M. sagu were shown that no differences. The nad2 gene on some accessions of M. sagu was inferred only one haplotype and the matK gene were inferred two haplotypes. The highest frequencies of the nucleotide in both nad2 and matK gene were calculated thymine (T). The amino acid leucine was the most common, accounting for 11.44% of haplotype-1 and 11.50% of haplotype-2. The amino acids alanine, cysteine, and methionine have the lowest rates, with 1.99% for haplotype-1 and 2.00% for haplotype-2. The evolutionary relationships were shown no mutation rates occur in the nad2 gene and lower mutation rates occur in the matK gene on M. sagu. Based on the genotype-2 (Sagu01, Sagu02, Sagu08, Sagu12, and Sagu15) is proposed to be new variety.